2023
DOI: 10.3390/solids4010001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Structural Comparison of Different Commercial Food Supplements for Silicon Uptake

Abstract: Various food supplements for silicon uptake were compared in terms of their structures and chemical compositions. In particular, we analyzed the silanol group content, which can be an indicator of the uptake of the siliceous species in the human body. We analyzed the commercial products Original Silicea Balsam®, Flügge Siliceous Earth Powder, Pure Colloidal Silicon, and BioSil® by applying various methods such as FTIR, 29Si NMR, and TGA. The Si-OH group content of the samples containing pure silica was the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…SiO 2 , as a silicic acid anhydride of monomeric ortho-silicic acid (H 4 SiO 4 ), is water-soluble and stable under aqueous conditions [14]. Indeed, ortho-silicic acid is known as the primary bioavailable form of silicon (Si) within the body [14,15]. It was reported that silicate, a group of polyatomic anions composed of silicon and oxygen in tetrahedral SiO 4 4− units, undergoes decomposition into bioavailable ortho-silicic acid under acidic conditions, such as gastric juice, and is absorbed into the body in this form [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SiO 2 , as a silicic acid anhydride of monomeric ortho-silicic acid (H 4 SiO 4 ), is water-soluble and stable under aqueous conditions [14]. Indeed, ortho-silicic acid is known as the primary bioavailable form of silicon (Si) within the body [14,15]. It was reported that silicate, a group of polyatomic anions composed of silicon and oxygen in tetrahedral SiO 4 4− units, undergoes decomposition into bioavailable ortho-silicic acid under acidic conditions, such as gastric juice, and is absorbed into the body in this form [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ortho-silicic acid is known as the primary bioavailable form of silicon (Si) within the body [14,15]. It was reported that silicate, a group of polyatomic anions composed of silicon and oxygen in tetrahedral SiO 4 4− units, undergoes decomposition into bioavailable ortho-silicic acid under acidic conditions, such as gastric juice, and is absorbed into the body in this form [14][15][16]. To date, clear information regarding the excretion fate of SiO 2 following oral intake and intracellular fates after cellular internalization remains unavailable.…”
Section: Introductionmentioning
confidence: 99%